Digital Leadership and Innovation in Indonesia’s Public Administration: Insights from the Govtech INA Digital Reform - Ariawan; Soemartono, Triyuni; Effendy, Khasan; Sukmana, Pandji (International Journal of Social Science and Religion (IJSSR), 2025)
This study explores how digital leadership influences innovation in Indonesia’s public sector amid the nationwide implementation of GovTech INA Digital and the updated Electronic Based Government System (SPBE). Using a qualitative, phenomenological design, the research draws on nine in-depth interviews with central and regional government officials, complemented by document analysis and observation. Thematic analysis revealed four key themes: visionary and communicative leadership, organizational digital capability, innovation culture and citizen co-creation, and institutional agility amid policy shocks. Visionary and communicative leadership enabled shared alignment across agencies, while empowerment-based leadership strengthened organizational capability. A culture of openness and co-creation fostered sustained innovation, although bureaucratic rigidity still limited rapid experimentation. Institutional reforms and crises particularly the 2024 PDNS ransomware incident tested leadership agility, revealing that adaptive leaders effectively transformed disruption into opportunities for systemic learning. The findings conceptualize digital leadership as an adaptive capability operating across behavioral, structural, cultural, and contextual pathways. The study contributes to digital governance theory by demonstrating how leadership behaviors and institutional contexts co-evolve to sustain innovation. Policy implications highlight the need for leadership development programs that combine strategic foresight, digital literacy, and participatory governance to enhance resilience and innovation in public administration.